The ice cream machine - Rubin, Adam, 1983- (Putnam : G. P. Putnam's Sons, 2022)
Contains six short stories by the author, each named "The Ice Cream Machine," but with different subtitles and themes, including stories about an evil ice cream man determined to ruin the joy of eating ice cream and a boy whose wish-making spirals out of control. Includes a writing activity and an ice cream recipe.